The Orexin/Receptor System: Molecular Mechanism and Therapeutic Potential for Neurological Diseases - Wang, Chunmei; Wang, Qinqin; Ji, Bingyuan; Pan, Yanyou; Xu, Chao; Cheng, Baohua; Bai, Bo; Chen, Jing (Frontiers in Molecular Neuroscience, 2018)
Orexins, also known as hypocretins, are two neuropeptides secreted from orexin-containing neurons, mainly in the lateral hypothalamus (LH). Orexins orchestrate their effects by binding and activating two G-protein–coupled receptors (GPCRs), orexin receptor type 1 (OX1R) and type 2 (OX2R). Orexin/receptor pathways play vital regulatory roles in many physiological processes, especially feeding behavior, sleep–wake rhythm, reward and addiction, and energy balance.Furthermore several reports showed that orexin/receptor pathways are involved in pathological processes of neurological diseases such as narcolepsy, depression, ischemic stroke, drug addiction, and Alzheimer’s disease. This reviewsummarizes the expression patterns, physiological functions, and potential molecular mechanisms of the orexin/receptor system in neurological diseases, providing an overall framework for considering these pathways from the standpoints of basic research and clinical treatment of neurological diseases.